Dynamic Meshing Characteristic Analysis of Wind Power Planetary Gear Train - Yang Haiwan; Mutellip Ahmat; Zhao Yang (Jixie chuandong)
The dynamic meshing study is essential for the wind turbine which works in a harsh condition,especially,the gear train will be destructed by the time-varying load.Taking a wind turbine helical planetary gear train as study object,considering the influence of a variety of clearance and friction on meshing,a FEM model is built.By using the nonlinear dynamics method,the variation law of the gear tooth root bending stresses in the processing of the planet gear meshing with the sun gear or the internal gear is studied,the influence of the rotating speed on the meshing impact stresses is analyzed.Though the analyzing,with the speed increasing,the meshing stresses curve could get ahead,the impact stress of gear box and drive shaft will increase,while the curve of the impact stress are overall forward.However,the impact stress can’t always increase with the impact speed increasing.